Rehabilitation of Facial Palsy Patient with Complete Denture - กาญจนนิตย์, ดนัย (Journal of Preventive Medicine Association of Thailand, 2018)
Using complete denture of patients with facial palsy always have some problem, due to poor neuromuscular control is considered to be the main reason for poor voluntary movements of lower mandible. That interfere denture retention, stability and their denture aesthetic. Case study: A 55-year-old female, she had facial palsy in 7 years, left facial nerve palsy due to malignant ostitisexterna with osteomastoiditis. She was diagnosed with left hearing loss that was treated by medicine, and surgical correction for lagothalomos. She would like to have a dental prosthesis. Extraoral examination revealed facial asymmetry, left corner of mouth fall with salivary drooling. Mandible slightly deviate to the right. Pronunciation were not clear at bilabial and labiodental articulation. Patient could not move mandible and bite follow doctor order. Occlusion was unstable due to facial muscle paralysis. Preliminary impressions was performed with alginate impression material and final impression with border molding was done by using silicone impression material. Occlusal rim was try in and anterior maxillary plane was set. Evaluation of occlusal vertical dimension was difficult due to poor control of mandibular movement patient and nonrepetitive. Therefore, doctor had to support and guide mandible during determine interarch relationship. Artificial teeth were arranged upon lingualize’s theory and buccal flange of left upper denture was expanded to support left cheek. Occlusion wax was changed to permanent prosthesis after patient satisfied with esthetic, pronunciation and biting. Surgical placement of osteointegrate implants was done. Lower denture should not be used at least 2 weeks. Four months after that, locators were attached to dental implants. Patient was scheduled for dental check up every 2 weeks for evaluateoral hygiene care. Follow up for 3 months after denture delivery, patient was satisfied with quality of chewing, esthetic, denture retention. Intraoral mucosa was within normal limit. Patient did not worry or feel any abnormalities around dental implants. Conclusion, this case report presented the rehabilitation of facial palsy patient with implants supported lower over denture. That prosthesis improves patient’s sense of well-being.